2021
DOI: 10.18178/ijiet.2021.11.9.1546
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Approaches and Its Impact on Student‘s Education — A Survey

Abstract: As mobile devices have become a part of our everyday life, there is a lot of research going on how to make this technology more productive for the students. Most of the research studies have indicated that, mobile devices are very useful for students while a few research studies negates its effectiveness. In this paper, we have presented the literature survey conducted on the use of mobile technologies in the field of Teaching and Learning (T&L). These studies are broadly classified into three areas: Impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Mobile devices can be used as auxiliary tools in the learning process [8]. Mobile devices allow students to connect to classes and training courses anywhere and any time provided that there is Internet access [9]. In addition, mobile technologies in education help to improve technical and communication skills, find answers to the questions of interest, develop the ability to cooperate with other people, allow learners to share knowledge, and, as a result, get better academic results [10].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile devices can be used as auxiliary tools in the learning process [8]. Mobile devices allow students to connect to classes and training courses anywhere and any time provided that there is Internet access [9]. In addition, mobile technologies in education help to improve technical and communication skills, find answers to the questions of interest, develop the ability to cooperate with other people, allow learners to share knowledge, and, as a result, get better academic results [10].…”
Section: Introductionmentioning
confidence: 99%
“…Study success is mainly influenced by the students' own involvement [6], their interest in studying, and an appropriate choice of a future career. The results of the admission procedure, the subsequent drop-out rate and timely completion of studies are influenced by social conditions of students, as demonstrated in a study conducted in Italy [7]. Graduates of technical and vocational secondary schools are disadvantaged in comparison to graduates of secondary grammar schools.…”
Section: Literature Reviewmentioning
confidence: 99%